Highly conducting corn starch doped ionic liquid solid polymer electrolyte for energy storage devices-RAFM 2022. (February 2023) - Konwar, Subhrajit; Singh, Abhimanyu; Singh, Pramod K; Singh, Ram Chandra; Rawat, Suneyana; Dhapola, Pawan Singh; Agarwal, Daksh; Yahya, MZA
In this study, a new biopolymer electrolyte (BPE) is successfully developed using corn starch complexed with ammonium iodide (NH4 I) as host, and low viscosity ionic liquid 1-Ethyl, 3-Methyl Imidazolium Thiocyanate (EMImSCN), as a plasticizer. This ionic liquid doped BPE shows high ionic conductivity of the order 10 −4 S/cm and electrochemical stability window more than 3 V, which is suitable for electrochemical application. The ionic transference number (tion ) of 0.98 confirms the system to be predominantly ionic in nature. Fourier transform infrared spectroscopy (FTIR) shows complex nature, while polarized optical microscopy (POM) gives us an idea about the semi-crystalline nature of BPE. Maximum conducting ionic liquid doped BPE sandwiched electric double layer capacitor (EDLC) and dye sensitize solar cell (DSSC) shows efficient performance.